Repair Strategies in Conversation between Father and Child in The Spilt Milk Podcast - Rifaa Ghassani Rahman; Pepen Priyawan; Erfan M. Fauzi (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
This research investigates the use of repair between father and child in the Spilt Milk Podcast. It classifies the types of repair strategies used by the father and the child in their conversation. Utilizing Schegloff, Jefferson, and Sacks's (1977) theory of repair organization, a qualitative method was applied. The data were collected through purposive sampling from a total of 178 episodes, which were grouped into three phases based on broadcast order: the early phase (Episodes 1-59), the middle phase (Episodes 60-119), and the final phase (Episodes 120-178). Five episodes were taken from each phase, resulting in Fifteen episodes analyzed in total. From a total of 43 data points found, the analysis focused on the most representative data points with characteristics specific to each type of repair. The most frequently used repair was Other-Initiated Other-Repair (OIOR), followed equally by Self-Initiated Self-Repair (SISR) and Other-Initiated Self-Repair (OISR), while the least frequent was Self-Initiated Other-Repair (SIOR). The findings suggest that OIOR was predominantly used by the father as a mechanism for supporting the child's language development through correction, reformulation, and vocabulary provision in naturally occurring daily interactions.